Refractive errors in a Brazilian population: age and sex distribution - Ferraz, Fabio H. [UNESP]; Corrente, Jose E. [UNESP]; Opromolla, Paula [UNESP]; Padovani, Carlos Roberto [UNESP]; Schellini, Silvana A. [UNESP] (Wiley-Blackwell, 2015)
PurposeTo determine the prevalence of refractive errors and their distribution according to age and sex in a Brazilian population.MethodsThis population-based cross-sectional study involved 7654 Brazilian inhabitants of nine municipalities of Sao Paulo State, Brazil, between March 2004 and July 2005. Participants aged >1year were selected using a random, stratified, household cluster sampling technique, excluding individuals with previous refractive or cataract surgery. Myopia was defined as spherical equivalent (SE) -0.5D, high myopia as SE -3.0D, hyperopia as SE +0.5D, high hyperopia as SE +3D, astigmatism as -0.5DC and anisometropia as 1.0D difference between eyes. Age, sex, complaints and a comprehensive eye examination including cycloplegic refraction test were collected and analysed using descriptive analysis, univariate and multivariate methods.ResultsThe prevalence of astigmatism was 59.7%, hyperopia 33.8% and myopia was 25.3%. Astigmatism had a progressive increase with age. With-the-rule (WTR) axes of astigmatism were more frequently observed in the young participants and the against-the-rule (ATR) axes were more frequent in the older subjects. The onset of myopia occurred more frequently between the 2nd and 3rd decades of life. Anisometropia showed a prevalence of 13.2% (95% CI 12.4-13.9; p<0.001). There was an association between age and all types of refractive error and hyperopia was also associated with sex. Hyperopia was associated with WTR axes (odds ratio 0.73; 95% CI: 0.6-0.8; p<0.001) and myopia with ATR axes (odds ratio 0.66; 95% CI: 0.6-0.8; p<0.001).ConclusionsAstigmatism was the most prevalent refractive error in a Brazilian population. There was a strong relationship between age and all refractive errors and between hyperopia and sex. WTR astigmatism was more frequently associated with hyperopia and ATR astigmatism with myopia. The vast majority of participants had low-grade refractive error, which favours planning aimed at correction of refractive error in the population.
Keywords: Associated factors; Brazil; Population study; Prevalence; Refractive error